2014
DOI: 10.1016/j.neuroimage.2014.05.070
|View full text |Cite
|
Sign up to set email alerts
|

tDCS-induced alterations in GABA concentration within primary motor cortex predict motor learning and motor memory: A 7T magnetic resonance spectroscopy study

Abstract: Transcranial direct current stimulation (tDCS) is a non-invasive brain stimulation technique that alters cortical excitability in a polarity specific manner and has been shown to influence learning and memory. tDCS may have both on-line and after-effects on learning and memory, and the latter are thought to be based upon tDCS-induced alterations in neurochemistry and synaptic function. We used ultra-high-field (7 T) magnetic resonance spectroscopy (MRS), together with a robotic force adaptation and de-adaptati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
191
5
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(207 citation statements)
references
References 31 publications
8
191
5
3
Order By: Relevance
“…The majority of these studies investigated neurometabolite changes in the motor cortex in young adults, reporting a consistent reduction of GABA after atDCS [31, 70, 75, 76], except for Tremblay et al [77]. The above finding was generally coupled with increased FC over the motor network [31, 39], indicating that these connectivity changes may be driven by a decrease in the inhibitory neurotransmitter.…”
Section: Mechanisms Of Network Modulation: Brain Neurometabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of these studies investigated neurometabolite changes in the motor cortex in young adults, reporting a consistent reduction of GABA after atDCS [31, 70, 75, 76], except for Tremblay et al [77]. The above finding was generally coupled with increased FC over the motor network [31, 39], indicating that these connectivity changes may be driven by a decrease in the inhibitory neurotransmitter.…”
Section: Mechanisms Of Network Modulation: Brain Neurometabolitesmentioning
confidence: 99%
“…Indeed, Stagg et al [76] estimated a decrease of around 12% of GABA levels in the motor cortex following motor atDCS and an inverse correlation with motor network FC [39]. Conversely, the effects of ctDCS on brain metabolites levels are less clear, one study reporting no effect [75], and one decreased GABA and Glu levels [70]. Age may modulate the effects of NIBS on brain neurometabolites.…”
Section: Mechanisms Of Network Modulation: Brain Neurometabolitesmentioning
confidence: 99%
“…Primary motor-cortex atDCS reduced local gamma-aminobutyric acid (GABA) concentration (Stagg et al, 2009; Kim et al, 2014) whereas ctDCS reduced both glutamate (Glu) and GABA concentrations in human cortex (Stagg et al, 2009). In contrast to Stagg et al (2009), in which stimulation was performed at rest, Kim et al (2014) observed no ctDCS effect on GABA when subjects were performing a motor adaptation task. Therefore, tDCS effects on neurotransmitter concentration may be task specific.…”
Section: Effects On Neurotransmissionmentioning
confidence: 99%
“…This is consistent with the findings of Hummel et al (2005) that JTT improvements persisted for at least 25 minutes after anodal tDCS. Changes in cortical excitability and intracortical inhibition have also been shown to persist after the stimulation is turned off (Ardolino et al , 2005, Stagg et al , 2009, Di Lazzaro et al , 2012, Bastani et al , 2013b, a, Kidgell et al , 2013, Kim et al , 2014, Moliadze et al , 2014.…”
Section: Discussionmentioning
confidence: 99%